2016
DOI: 10.1364/oe.24.028704
|View full text |Cite
|
Sign up to set email alerts
|

Low loss Type II regenerative Bragg gratings made with ultrafast radiation

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Another promising mechanism for reconfigurating phase‐changing nanophotonic structures is the glass relaxation and reflow under high‐temperature annealing driven by stress generation around the laser‐structured regions . Similar effects are anticipated in polymers with rubber–glass transitions where the strain defines the material response in an elastic or inelastic manner allowing for visco‐elastic flows to occur at high strains.…”
Section: Reversible Tuningmentioning
confidence: 86%
“…Another promising mechanism for reconfigurating phase‐changing nanophotonic structures is the glass relaxation and reflow under high‐temperature annealing driven by stress generation around the laser‐structured regions . Similar effects are anticipated in polymers with rubber–glass transitions where the strain defines the material response in an elastic or inelastic manner allowing for visco‐elastic flows to occur at high strains.…”
Section: Reversible Tuningmentioning
confidence: 86%
“…The results from the previous section demonstrate that by blocking the π-shift one can fabricate quite symmetric Type II FBGs using a 1st-order mask, even when the inscription is performed at some distance from the mask, i.e., at L ~450 m. However, our previous results demonstrated that the long-term stability of Type II FBGs at high temperatures (i.e., ~1000°C) was improved when a 3rd-order mask was used for the inscription [64]. Taking into account the fact that this paper focuses on stable π-shifted Type II FBGs for extreme environments, the remainder is dedicated to studying the properties of gratings produced with a 3.21 mm pitch mask.…”
Section: Inscription Of π-Shifted Type II Fbgs In Smf-28 Fiber Using mentioning
confidence: 86%
“…When the fibre is pre-annealed (before FBG writing) at high temperature (5 h at 1100°C), Type II fs-infrared (IR) FBGs are stable up to 1200°C during 20 h [60]. Following this view, regeneration can also improve fs-FBG performance to some extent [40,61]. In conventional single mode fibres (SMFs, Ge-doped silica glass), the point-to-point voids FBG (Type III fs-FBGs) have slight loss of reflectivity (typically 20% of its initial strength) in less than 20 h at 1000°C, before stabilizing [62].…”
Section: Femtosecond Fbgs (Type II and Iii Fbgs)mentioning
confidence: 99%